Traduire dans un système autoritaire en temps de crise : les représentations des événements polonais de 1980–1981 dans la presse officielle polonaise à destination des lecteurs occidentaux - Regina Solová (Romanica Wratislaviensia)
The aim of this paper is to study the modes of representation of reality in original texts and their translations published under the constraints of an authoritarian regime in times of crisis. The study was based on the presupposition that the description of reality is filtered through the idiosyncrasies of the authors of the original texts and their translations, as well as through the constraints of the source system at a particular moment in its history. The nature of the shifts in representations of reality was tested on the example of sixteen issues of the magazine Polska and their English (Poland) and French (La Pologne) translations, reporting on the Polish events of 1980–1981. The study showed that the three language versions of the magazine Polska, which were supposed to be identical, represented reality in slightly different ways and that these representations were the result of several superimposed subjective visions of their authors, conditioned by various factors such as the speed of change, the lack of temporal distance, the individual attitude to events or the translator’s competence.